Finding Religious Moderation in Pondok Pesantren: Religious Moderation Education at Pondok Pesantren in Central Kalimantan - Surawan, Surawan; Anshari, Muhammad Redha; Azmy, Asmail; Adi, Muhammad Iqbal Purnama (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
This study aims to explore the role of Kyai and Ustadz in implementing religious moderation education at Pondok Pesantren in Central Kalimantan. The study was conducted at four Pondok Pesantren in Central Kalimantan, namely Pondok Pesantren Hidayatul Insan, Pondok Pesantren Hasanka, Pondok Pesantren Darul Ulum, and Pondok Pesantren Darul Amin Sampit. This study is a qualitative study with an interpretive paradigm. The study was conducted from April to September 2021. Data was obtained through observation, interviews and documentary studies. Informants in this study were educators in Pondok Pesantren, namely Kyai, Ustadz, and teachers who teach. The data obtained were then analysed using interactive qualitative analysis techniques: data collection, data reduction, data display, and conclusion drawing. This study found that there are five roles of Kyai and Ustadz in religious moderation education, namely the role of conservator, innovator, the role of transmitter, the role of a transformer, and role of organiser. Departing from these findings, it can be concluded that there is a connectivity between academic and managerial dimensions in implementing religious moderation education at Pondok Pesantren in Central Kalimantan. At this level, Kyai and Ustadz not only play a role in providing understanding and knowledge regarding religious moderation but also carry out managerial activities so that religious moderation education can be carried out and be successful.Keywords: